Not So Sweet: Impacts of a Soda Tax on Producers - Judite Goncalves; Roxanne Merenda; Jo\~ao Pereira dos Santos (Institute of Labor Economics (IZA), 2023)
Portugal introduced a sugar-sweetened beverages (SSB) tax in 2017. This study uses unique administrative accounting data for all SSB producers/importers in Portugal, and an event study design with bottled water firms as the primary comparison group, to assess the causal impacts of the tax on multiple firm-level outcomes. We find a 6.8% average decrease in domestic SSB sales, vis-à-vis bottled water. The soda tax hindered SSB firms' financial health, namely net income, ability to convert receivables into cash, and liabilities. SSB producers/importers did not decrease wages, cut jobs, or modify their workforce towards higher R&D capacity. Forgone corporate income tax appears negligible compared to the government revenue generated by the tax itself.
Keywords: H25; H51; I18; 330; sugar tax; soda tax; firm-level; sin taxes